Consumer knowledge and attitude towards orange-fleshed sweetpotato (OFSP) puree bread in Kenya - Wanjuu, C.; Bocher, T.; Abong, G.O.; Low, Jan W.; Mbogo, D.; Heck, S.; Muzhingi, T. (Walter de Gruyter GmbH, 2019)
OFSP is being used as an ingredient of baked products and can be a source of pro-vitamin A. Information about OFSP puree bread consumer profile is limited. The current study investigates the consumer socio-demographics, knowledge, practices and attitude towards OFSP puree bread in Kenya. A total of 1024 consumers were interviewed from Nairobi, Kiambu, Kajiado, Kisumu and Kakamega counties. The OFSP bread is purchased by 60% female respondents above 30 years old, who have a university education (79%), formally employed (93%), therefore, middle to high-income earners. Before consumption, 42% of the consumers stored their bread in the refrigerator while 38% stored in the open, and 20% in cupboards. Consumers agree that the OFSP bread could be a good source of energy, vitamins, especially Vitamin A (94%). The acceptance ratings of OFSP bread ranged from 7.37 to 7.65 on a 9-score hedonic scale, hence “liked moderately.” There was a significant relationship between socio-demographics, knowledge about the root, the bread and the overall acceptance of the OFSP puree bread. Consumers were willing to pay more for the OFSP bread based on potential nutritional benefits. There was a significant relationship between consumer demographics and willingness to pay for OFSP puree bread.